Enhancing intercultural competence and global engagement through COIL: A narrative literature review - Shafia Aulia Rakhma; Aulia Zilmi Kafah; Muhammad Soali (Concept : Community Concern for English Pedagogy and Teaching, 2025)
This study investigates the impact of Collaborative Online International Learning (COIL) on enhancing intercultural competence, digital literacy, and global citizenship among higher education students. Using a narrative literature review supported by the frameworks of social constructivism, transformative learning, and technological determinism, this research synthesizes findings from 22 peer-reviewed studies. The results show that COIL promotes inclusive international learning by enabling cross-cultural collaboration without physical mobility. It also highlights COIL’s potential to democratize access to global education, support the development of 21st-century competencies, and foster reflective, interculturally aware learners. However, challenges such as technological inequality, time zone coordination, and institutional readiness remain significant. The study concludes that with strategic implementation and ongoing support, COIL can evolve into a sustainable and transformative model for global learning in higher education. Keywords: COIL; Global Awareness; Learning Materials; Global Learning; Intercultural Competence; Virtual Collaboration